PEMBINAAN KHUTBAH DAN IMAM SHALAT JUM’AT PADA MASYARAKAT DESA SEBANGUN - Aslan Aslan; Rusiadi Rusiadi (Jurnal Pengabdian Kepada Masyarakat, 2021)
Categories to become a sermon and an imam need to know about several pillars, conditions, and others so that when they become Friday sermons and Imams, these things have been mastered as well as possible. The purpose of community service carried out in Sebangun Village is to understand the community so that when they become a sermon and an Imam, they look at the age category, but many things need to be considered. The results of community service that have been carried out need further guidance so that from the material presented and the dilemmas felt by the Sebangun community related to the sermon and the Imam; there is no difference because the purpose of community service with this theme is to provide an understanding so that there is a difference is not enmity, but it is nature